Conceptual Approach to Body Fluids and Edema, Education Determines Clinical Outcomes in Nephrotic Syndrome Management (Iranian Journal of Kidney Diseases, 2021)
The objective of our paper is to reemphasize the importance of critical thinking in clinical practice and education in the field of internal medicine using the example of edema. We provide an in-depth and interactive investigation of physiological concepts as a foundation for the understanding of body fluid dynamics. Four fundamental concepts described are the hydrostatic and oncotic pressure gradients, capillary permeability, and lymphatic drainage. Furthermore, we visit the causes of edema in nephrotic syndrome. Traditional teaching considers hypoalbuminemia as a primary cause of edema formation in nephrotic syndrome. It has been proven that other etiologies causing edema include salt and water retention by the kidneys and a possible increase in capillary permeability are more important causes in the development of edema in nephrotic syndrome.